Prevention of Pollution of the Marine Environment from Vessels - Karim, Md Saiful (Springer, 2015)
This book examines the role of The International Maritime Organization (IMO) in the prevention and control of pollution of the marine environment from vessels with a particular reference to the current north-south tensions regarding the strategy for combating climate change in the maritime sector as well as the prevention of marine pollution from the ship-breaking industry.